Cost of behavioral weight loss programs implemented in clinical practice: The POWER trial at Johns Hopkins. Issue 1 (11th March 2019) - Daumit, Gail L; Janssen, Ellen M; Jerome, Gerald J; Dalcin, Arlene T; Charleston, Jeanne; Clark, Jeanne M; Coughlin, Janelle W; Yeh, Hsin-Chieh; Miller, Edgar R; Durkin, Nowella; Louis, Thomas A; Frick, Kevin D; et al.
Abstract : A weight loss program for people with obesity that was administered via telephone and over the internet only was less costly per pound lost than a program that included in-person component. Abstract: Obesity presents an important public health problem that affects more than a third of the U.S. adult population and that is associated with increased morbidity, mortality, and costs. Previously, we documented that two primary care-based weight loss interventions were clinically effective. To encourage the implementation of and reimbursement for these interventions, we evaluated their relative cost-effectiveness. We performed a cost analysis of the Practice-based Opportunities for Weight Reduction (POWER) trial, a three-arm trial that enrolled 415 patients with obesity from six primary care practices. Trial participants were randomized to a control arm, an in-person support intervention, or a remote support intervention; in the two intervention arms, behavioral interventions were delivered over 24 months, in two phases. Weight loss was measured at 6, 12, and 24 months. Using timesheets and empirical data, we evaluated the cost of the in-person and remote support interventions from the perspective of a health care system delivering the interventions. A univariate sensitivity analysis was conducted to evaluate uncertainty around model assumptions. All comparisons were tested using independent t -tests. Cost of the in-person intervention was higher at 6 months ($113 per participant per month and $117 per kg lost) than the remote support intervention ($101 per participant per month and $99 per kg lost; p < .001). Costs were also higher for the in-person support intervention at 24 months ($73 per participant per month and $342 per kg lost) than for the remote support intervention ($53 per participant per month and $275 per kg lost; p < .001). In the sensitivity analyses, cost ranged from $274/kg lost to $456/kg lost for the in-person support intervention and from $218/kg to $367/kg lost for the remote support intervention. A primary care weight loss intervention administered remotely was relatively more cost-effective than an in-person intervention. Expanding the scope of reimbursable programs to include other cost-effective interventions could help ensure that a broader range of patients receive the type of support needed.